Occlusive Disease of Intracraneal Carotid - Lanterna, Washington; Lanfranconi, Armando; Burjel, Jorge (Cirugía del Uruguay, 1980)
Case material consists in a series of 25 patients who suffered from cerebrovascular accidents of extracranial origin. The frequency_ of this disease is emphasized and preventive measures are advisable. 'he different clinical · types of ischemic events are described, surgical indications are discussed and stress is Iaid on the importance of clinical - angiographic correlation.